2017
DOI: 10.1038/ismej.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Annual community patterns are driven by seasonal switching between closely related marine bacteria

Abstract: Correction to: The ISME Journal 2017; 11: 1412−1422. doi: 10.1038/ismej.2017.4 In the original online publication of this article the incorrect file was uploaded as supplementary information. The correct file has now been added to the online version of the article. The publishers would like to apologise for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…There are many taxa that are strongly correlated with these measured environmental variables. These findings follow previous work that has shown that the environment plays a key role in selecting for the microbial taxa present in a location in marine environments (40,41).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…There are many taxa that are strongly correlated with these measured environmental variables. These findings follow previous work that has shown that the environment plays a key role in selecting for the microbial taxa present in a location in marine environments (40,41).…”
Section: Resultssupporting
confidence: 92%
“…Our observation that members of abundant and ubiquitous groups are indicators of geospatial location suggest that these biogeographic patterns may be robust to seasonal changes. Despite longitudinal research showing how dominant bacteria of a system persist throughout the year (40,41,(45)(46)(47), more work is needed to observe exactly how abundant taxa may proportionally stabilize their community composition across large spatial scales and after seasonal changes.…”
Section: Figmentioning
confidence: 99%
“…), Flavobacteriaceae (NS5 marine group) and γ-proteobacteria SAR86 clade. As significant free-living or particle-associated constituents found in coastal and/ or open-ocean waters throughout the world, and whose populations are well known to vary temporally [87][88][89], the occurrence of such taxa may reflect the common ingestion of local, environmentally driven microbial consortia, as discussed earlier. Indeed, bivalves in this study were sampled from a particularly dynamic region that, as part of the broader eastern Great Australian Bight (GAB), is marked by significant wind-driven summer upwelling and winter downwelling events that influence nutrient availability and mixing [90,91].…”
Section: Discussionmentioning
confidence: 94%
“…), Flavobacteriaceae (NS5 marine group) and γ-proteobacteria SAR86 clade. As signi cant free-living or particle-associated constituents found in coastal and/or openocean waters throughout the world, and whose populations are well known to vary temporally [89, 90,91],…”
Section: Discussionmentioning
confidence: 99%